Vibration from freight trains fragments sleep: A polysomnographic study - Smith, Michael G. (Sci Rep, 2016)
As the number of freight trains on railway networks increases, so does the potential for vibration exposure in dwellings nearby to freight railway lines. Nocturnal trains in particular are of particular importance since night-time exposure may interfere with sleep. The present work investigates the impact of vibration and noise from night-time freight trains on human sleep. In an experimental polysomnographic laboratory study, 24 young healthy volunteers with normal hearing were exposed to simulated freight pass-bys with vibration amplitudes of 0.7 and 1.4 mm/s either 20 or 36 times during the night. Stronger vibrations were associated with higher probabilities of event-related arousals and awakenings (p < 0.001), and sleep stage changes (p < 0.05). Sleep macrostructure was most affected in high vibration nights with 36 events, with increased wakefulness (p < 0.05), reduced continual slow wave sleep (p < 0.05), earlier awakenings (p < 0.05) and an overall increase in sleep stage changes (p < 0.05). Subjects reported sleep disturbance due to vibration (F(4,92) = 25.9, p < 0.001) and noise (F(4,92) = 25.9, p < 0.001), with the number of trains having an effect only for the 0.7 mm/s condition (p < 0.05). The findings show that combined vibration and noise from railway freight affects the natural rhythm of sleep, but extrapolation of significance for health outcomes should be approached with caution.